Botulinum Toxin Treatment for Thoracic Outlet Syndrome Induced by Subclavius Muscle Hypertrophy - Francesco Cavallieri; Stefano Galletti; Valentina Fioravanti; Elisa Menozzi; Sara Contardi; Franco Valzania (NeuroSci, 2021)
Thoracic outlet syndrome (TOS) is frequently caused by bone abnormalities and congenital or acquired soft-tissue alterations. Among these, isolated Subclavius Muscle (SM) hypertrophy represents a rare condition that could lead to a reduction in costoclavicular space and brachial plexus compression. A 47-year-old forest ranger with a history of gun shooting during animal hunting and training sessions of skeet shooting for 20 years developed TOS due to ultrasonography-detected isolated SM hypertrophy, successfully treated with an ultrasound-guided Botulinum Toxin (BTX)-A injection. In our patient, ultrasonography of the brachial plexus has allowed SM hypertrophy to be recognized and to perform BTX-A injection just in the muscle, with a complete resolution of the symptoms.